2011
DOI: 10.3844/ajassp.2011.724.735
|View full text |Cite
|
Sign up to set email alerts
|

Does Organizational Culture Influence the Innovativeness of Public-Listed Housing Developers?

Abstract: Problem statement:The benefits of innovation and the need to be innovative have been highlighted by many. However, it is doubtful whether the players in the housing industry, in particular housing development firms, have the characteristics that are favorable for innovation. This study investigates the relationship between organizational culture and the innovativeness of public-listed housing developers in Malaysia. Approach: A survey was conducted among all housing developers registered with the Bursa Malaysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 63 publications
(94 reference statements)
2
19
1
Order By: Relevance
“…There are some reasons to explain why our findings contradict with Yusof and Abidin (2011) result. First of all, our sample was drawn from all housing developers registered with the Real Estate and Housing Developers Association; including the public-listed ones.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…There are some reasons to explain why our findings contradict with Yusof and Abidin (2011) result. First of all, our sample was drawn from all housing developers registered with the Real Estate and Housing Developers Association; including the public-listed ones.…”
Section: Resultscontrasting
confidence: 56%
“…There is however inconsistency in some of these results (Jantan et al, 2003). For example, while previous studies have shown that organizational culture influences innovativeness (Hurley and Hult, 1998), recently, Yusof and Abidin (2011) find that culture does not significantly influence the innovativeness among Malaysian public-listed housing developers. Similarly, Brandyberry (2003) empirically examines the influence Science Publications AJAS of five firm characteristics on the adoption of architectural software (CAD).…”
Section: Introductionmentioning
confidence: 68%
“…Aspects of innovativeness are among the most frequently exercised conversations relating to economic progress and prosperity (Nasierowski and Arcelus, 2012). There is no scarcity of innovation research, a comparatively small number of studies focus on innovativeness (Yusof and Abidin, 2011). There is also an apparent lack of a coherent perspective on innovativeness (Goswami and Mathew, 2005).…”
Section: Organizational Innovativenessmentioning
confidence: 99%
“…The study of organizational culture has produced valuable theoretical and practical results in a wide range of fields [17][18][19] among many others. Specialized literature contains a variety of models for describing organizational culture, based on existing research.…”
Section: Organizational Culture and The "Competing Values Framework"mentioning
confidence: 99%